The effect of Service Quality on Behavioral Intentions Through Satisfaction and Customer Perceived Value - Amir Mohamad Fakour; Sima Hadadian; Yegane Kelidari (کاوش‌های مدیریت بازرگانی, 2015)
The main purpose of this paper is investigating the effect of service quality on positive behavioral intentions through satisfaction and customer perceived value. The design of this study is descriptive-correlational and the population includes the customers of Samen Al-hojaj finance and credit institution in Mashhad. The calculated sample was 304,selected via simple random sampling method. The initial model was designed following the literature review. As the next step, the model was modified using the experts’ view. The data collection instrument was questionnaire. To test the model, structural equation modeling was used via Amos software. Results showed that service quality has an influence on positive behavioral intentions directly and indirectly through satisfaction and customer perceived value. It should be noted that indirect impact of service quality on positive behavioral intentions is more significant than its direct impact. Additionally, it was found that the qualification index in providing services has the greatest impact on service quality.